Consequences of the European Team Championships' new rules on pole vault - Theodorou, A.; Skordilis, E. (International Journal of Performance Analysis in Sport, 2010)
Over the 2009 European Team Championship, the European Athletics Association proceeded to a modification of Pole Vault rules according to which, each competitor was entitled to a maximum of 4 aggregate fouls throughout the competition. The purpose of the study was to examine the effects of new rules implementation on men's and women's Pole Vault competition. The 2008 and 2009 European Team Championships results for the Super and First Leagues (n = 48; 24 males & 24 females) were compared. The dependent variables were: Athlete's Final Height (AFH), Number of Efforts (NE), Successful Efforts (SE), Failed Efforts (FE) and Efforts Forgoed (EF). Men's AFH remained unchanged (0.04%). NE reduced by 1.92% while the percentile SE/FE distribution changed favourably towards the SE (40.65%/59.35% for 2008 vs 43.42%/56.58% for 2009). Women's AFH remained unchanged (+ 0.24%). NE decreased significantly by 16.28%, while the percentile SE/FE distribution changed favourably towards the SE (44.70%/55.30% for 2008 vs 47.21%/52.79% for 2009). Overall, the restriction in Pole Vault efforts seems to have had a slightly positive effect on men's and women's performance.